GREEN LOCAL WISDOM, THE DUTY TO REMEMBER, AND RECOGNITION OF BEAUTY IN SERAT CENTHINI - Inandiak, Elizabeth D. (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2019)
Serat Centhini is often described as the encyclopedia of Java. The poem was indeed written at the beginning of the 19th century, but the “plot” takes place at the 17th century, a pivotal time in Central Java where Islam spreads and settles, while the older cults are still alive. Serat Centhini acts as a colossal cultural laboratory which tests the ancestral knowledge and traditions in the light of the new science of Islam. Will these knowledge and traditions become obsolete and disappear on their own? Will they persist because of their universal foundations, or because of their deep roots in local wisdom, or their capacity to adjust and embrace a new form? Will they enter into conflict or go underground? The experimentation works two ways: will the new science of Islam be flexible enough to accommodate the ancestral world view in its modernity? This paper seeks to present three brilliant cultural strategies successfully put to test in the Centhini laboratory, in their ability to transcend time, and embrace social and religious transformations: green local wisdom, the duty to remember, and recognition of Beauty.